Cytological Study of Palpable Breast Lump Presenting in Eastern Nepal - Singh, M.; Kafle, S.U.; Jha, K.K. (Birat Journal of Health Sciences, 2017)
Introduction Breast lump constitute significant proportion of surgical cases. It is necessary to distinguish between benign and malignant lesions for definite treatment. Fine needle aspiration cytology (FNAC) is widely adopted for the pathologic assessment because of its accuracy and ease of use. Objective The present study was done to find out the frequency of various patterns of breast lesion on FNAC and the common age - group in which the lesions occurs. Methodology This is a four years retrospective study carried out from December 2011 to January 2016. The 553 patients who presented with palpable breast lump, and have underwent FNAC irrespective of age and sex were included in the study. All the datas were collected from the patients record form. FNAC findings were correlated with the data from histopathology records to determine the sensitivity and specificity of FNAC. Results The majority of the patients were female and majority of lump was benign. Fibroadenoma was the most common lesion accounting for 32.18 % of all lesions and most commonly occurring in age group between 21 -30 years. Fibrocystic disease was second common benign lesion accounting for 30.56 also commonly accounting in the age group 21- 30 years. Carcinoma breast was seen in 5.42 % of cases (30/553) occurring most commonly in the female patients above 30 years of age. Most common age group for gynaecomastia in male breast was 11 – 20 years. Conclusion FNAC is a rapid and safe method for diagnosing palpable breast lump into benign and malignant categorizes and thus avoiding unnecessary surgery. Birat Journal of Health Sciences 2016 1(1): 27-32